New transport services for next-generation SONET - Cavendish, D. (IEEE Communications magazine)
SONET/SDH systems have been the preferred transport technology over fiber optics for almost two decades now. Carriers have developed extensive expertise in operating, managing, and developing business models for these systems. Manufacturers' technical expertise in such systems has increased to a deep understanding of what transport over fiber is about. In short, SONET/SDH can be called a mature transport technology. Out of this mature expertise, new techniques for bettering transport over fiber services have appeared. These techniques are likely to considerably reshape the next generation of SONET/SDH systems in many aspects: new transport techniques, new transport services, new management systems and business models. We describe several new transport techniques, and discuss their impact on the creation of new transport services for next-generation SONET/SDH systems.